2021
DOI: 10.3390/jcm10235687
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Pneumothorax Might Not Be ‘True’ Recurrence

Abstract: Objectives: To date, there is no consensual definition of what constitutes a postoperative recurrence of primary spontaneous pneumothorax (PSP), despite there being many studies reporting a high incidence of recurrence. This study aims to describe the long-term recurrence rates of pneumothorax and to suggest a possible way to differentiate recurrence events based on temporal patterns. Methods: This single-center study retrospectively evaluated all postoperative recurrence of PSP from January 2007 to May 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, a larger coverage area could help minimize the risk of early neo-bullae formation near the staple line. In addition, early recurrence in the PGA group may be related to the healing process or detachment of the coverage materials from the lung [24]. To understand different recurrence-free intervals, further studies including more patients with follow-up and sequential radiologic examination are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a larger coverage area could help minimize the risk of early neo-bullae formation near the staple line. In addition, early recurrence in the PGA group may be related to the healing process or detachment of the coverage materials from the lung [24]. To understand different recurrence-free intervals, further studies including more patients with follow-up and sequential radiologic examination are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue in the Journal of Clinical Medicine (JCM) brings together a series of high-quality scientific contributions that try to weave a common thread that extends from the etiology to the treatment of SP [ 1 , 2 , 3 , 4 , 5 ]. The covered topics distinctly point out the issues related to PSP and SSP, although both diseases present some similar approaches in the diagnostic–therapeutic path.…”
mentioning
confidence: 99%
“…There is not a clear and established definition of postoperative recurrence of pneumothorax. Woo and colleagues attempted in their study to suggest a new classification system for the postoperative recurrence of SP [ 4 ] and tried to identify risk factors that could be related to a second recurrence. Following other reports, authors concluded that a pneumothorax occurring within 30 days from surgery should not be considered a true recurrence but part of the healing process [ 4 , 28 , 29 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation